2022
DOI: 10.3390/nu14030572
|View full text |Cite
|
Sign up to set email alerts
|

Sports Nutrition and Food Knowledge among Malaysian University Athletes

Abstract: Sports nutrition and food knowledge can influence athletes’ dietary intake, potentially affecting athletic performance. Limited studies have been conducted to identify sports nutrition and food knowledge among Malaysian university athletes. This study aimed to determine Malaysian university athletes’ knowledge of sports nutrition and food, and their reference sources and preferred sports nutrition education programme. Seventy athletes (52.9% females, mean weight = 61.8 kg; height = 1.66 m) aged 18.5–22.4 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…Comparatively, the scores of athletes were lower in the macronutrients and micronutrients sections than in the hydration and periodization sections, whose scores were above the overall mean. In the case of hydration, our observations coincide with some studies [ 34 , 40 , 49 ], but differ from others [ 9 , 11 ]. Athletes should clearly improve their NK, mainly in the areas of macronutrients and micronutrients, since it was similar to that of groups representing the community and far below the knowledge demonstrated by STT.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Comparatively, the scores of athletes were lower in the macronutrients and micronutrients sections than in the hydration and periodization sections, whose scores were above the overall mean. In the case of hydration, our observations coincide with some studies [ 34 , 40 , 49 ], but differ from others [ 9 , 11 ]. Athletes should clearly improve their NK, mainly in the areas of macronutrients and micronutrients, since it was similar to that of groups representing the community and far below the knowledge demonstrated by STT.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, when athletes and non-athletes were aggregated according to their level of education, and subgroups with similar education levels compared for their NUKYA scores, such scores were coherent, supporting the association of education with NK. The main sources of information reported by athletes were families, dietitians, physiotherapists, coaches, and Internet; in general, these coincide with the sources reported in more recent studies [ 32 , 40 , 42 ] and are quite different from those reported in older studies [ 41 , 55 ]. Dietitians were reported as one of the main sources of information (57%), although only 13% of athletes consistently attended the dietitian office.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Most of the athletes also did not consume milk or calcium supplements regularly. A healthy diet that includes calcium and vitamin D is important for maintaining bone health [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A purposive sampling method was employed to select the participants due to the difficulties in accessing the entire sampling frame caused by the strict MCO, a common issue experienced by many studies carried out in Malaysia during the COVID-19-related lockdown period [ 28 , 29 ]. Theoretically, this is justified by a number of prior studies which showed the acceptability of a purposive sampling approach in sampling marginalized populations [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%